2017
DOI: 10.1016/j.kint.2017.03.037
|View full text |Cite
|
Sign up to set email alerts
|

The loss of Krüppel-like factor 15 in Foxd1+ stromal cells exacerbates kidney fibrosis

Abstract: Large epidemiological studies clearly demonstrate that multiple episodes of acute kidney injury contribute to the development and progression of kidney fibrosis. Although our understanding of kidney fibrosis has improved in the past two decades, we have limited therapeutic strategies to halt its progression. Myofibroblast differentiation and proliferation remain critical to progression of kidney fibrosis. Although canonical Wnt signaling can trigger activation of myofibroblasts in the kidney, mediators of Wnt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Conversely, the overexpression of KLF15 inhibited phospho-β-catenin (Ser552) expression in Wnt1-treated cells. 32 The present findings demonstrate that high glucose treatment can induce Wnt4 activation in renal tubular epithelial cells, thereby activating the Wnt/β-catenin pathway to induce increased expression of α-SMA and decreased expression of E-cadherin. The exogenous administration of the Wnt blocker recombinant human dickkopf-related Protein-1(DKK-1) can attenuate the expression of collagen-1 and FN by inhibiting the activation of β-catenin signalling in a unilateral ureteral obstruction mouse model.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Conversely, the overexpression of KLF15 inhibited phospho-β-catenin (Ser552) expression in Wnt1-treated cells. 32 The present findings demonstrate that high glucose treatment can induce Wnt4 activation in renal tubular epithelial cells, thereby activating the Wnt/β-catenin pathway to induce increased expression of α-SMA and decreased expression of E-cadherin. The exogenous administration of the Wnt blocker recombinant human dickkopf-related Protein-1(DKK-1) can attenuate the expression of collagen-1 and FN by inhibiting the activation of β-catenin signalling in a unilateral ureteral obstruction mouse model.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies have demonstrated that the loss of a Kruppel‐Like Factor 15 (KLF15) in cultured mouse embryonic fibroblasts, a kidney‐enriched zinc‐finger transcription factor, activated canonical Wnt/β‐catenin signalling, increased profibrotic transcription, and enhanced proliferation following treatment with a Wnt1 ligand. Conversely, the overexpression of KLF15 inhibited phospho‐β‐catenin (Ser552) expression in Wnt1‐treated cells …”
Section: Discussionmentioning
confidence: 98%
“…Input (2%) of whole-cell lysates was immunoblotted with KLF15, WT1, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) to detect protein expression as previously reported. 14…”
Section: Coimmunoprecipitationmentioning
confidence: 99%
“…9,12 As such, we hypothesized that the induction of human KLF15 specifically in the podocyte might prevent podocyte injury in proteinuric murine models. Because KLF15 is expressed in several cell types in the kidney, 9,14 we initially generated mice with podocyte-specific expression of human KLF15 (KLF15) using the "tet-on" system on the FVB/N background, where the binding of chimeric tetracycline transactivator protein (rtTA) to tet-operator and gene activation only occurs in the presence of DOX (Supplemental Figure 1A). We bred the TRE-KLF15 mice with the Podocin-rtTA (PODTA) mice to generate mice with podocyte-specific expression of KLF15 in the setting of DOX administration on the FVB/N background strain.…”
Section: Podocyte-specific Klf15 Induction In Micementioning
confidence: 99%
“…Previous studies have demonstrated that KLF15 regulates fibrotic factors contributing to kidney fibrosis in different kidney injury models (13, 28). It is reported that excessive collagen accumulation is mainly restricted to vascular adventitia (6, 17).…”
Section: Discussionmentioning
confidence: 99%